Response of Global Forest Management to Changes in Wood Demand - Bartlomiej Arendarczyk; Sam Rabin; Daniel Bampoh; Almut Arneth; Mark Rounsevell; Peter Alexander (Global Change Biology, 2025)
Global wood harvests have steadily increased over the last several decades and are projected to continue growing to match demand for wood products. How forest managers respond to changes in wood demand depends not just on timber prices and production costs but also on competition with other land uses, changes in forest productivity, and land use policies. Wood demand projections are sensitive to assumptions about socioeconomic development, including population growth, economic growth, and policy changes. Using a spatially detailed, process‐based land use model (LandSyMM), we simulate global wood demand, harvests, and forest management intensity under a range of future socioeconomic (Shared Socioeconomic Pathways; SSPs) and climate (Representative Concentration Pathways; RCPs) scenarios. Wood demand is projected for each country using a price‐elastic demand system that models changes in demand for industrial roundwood and wood fuel in response to changes in countries' incomes and endogenously modelled wood prices. Competition for land between forestry and agriculture, including for food and animal feed, is explicitly represented. We find that future wood harvests and forest management intensity vary considerably between scenarios. Different regions show heterogeneous responses to changes in wood demand, with global demand increasing between 27% (SSP1‐RCP2.6) and 102% (SSP3‐RCP7.0) by 2100. The results suggest that additional wood harvests will primarily be met through intensification of forest management and an increase in potential yields arising from climate change and CO 2 fertilisation. However, interactions between extreme events, nutrient limitations, and CO 2 ‐driven productivity gains remain uncertain and are not fully captured in the modelled results. Understanding how global forest management will change and its impact on forest structure, species composition, and carbon storage is critical in addressing climate change mitigation and biodiversity protection.

Mapping the shared socio-economic pathways onto the Nature Futures Framework at the global scale - Peter Alexander; Roslyn Henry; Sam Rabin; Almut Arneth; Mark Rounsevell (Sustainability Science, 2023)
The Nature Futures Framework (NFF) was developed for the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES) to explore scenarios that represent a diversity of positive relationships between humans and nature. Widely used in global environmental assessments, the shared socio-economic pathways (SSPs) in combination with the representative concentration pathways (RCPs) were developed for climate change assessments. However, the relationship at a global level between the SSP–RCP scenario outcomes and the framing of the NFF around three value perspectives—Nature for Nature, Nature for Society, and Nature as Culture—has not been established. Here, we demonstrate a method to map onto the NFF value perspectives results from alternative SSP scenarios, each paired with an RCP consistent with the SSP storyline. For each of the NFF value perspectives, multiple elements were identified, each represented by one or more nature-focused indicators. Values for these indicators, for the different SSP scenario outcomes, were derived from an existing application of a global land system model, LandSyMM. A score for each indicator is estimated by comparing the indicator values against a normative target range. We find that only SSP1 provides greater benefits for Nature as Culture and Nature for Society relative to a 2010 baseline. Overall, the SSP scenarios provide fewer benefits for Nature for Nature, consistent with a bias towards the provision of material over non-material ecosystem services. The results demonstrate that the SSP–RCP scenario framing captures some, but not all, of the dimensions of nature and that alternative scenario framings, such as the NFF, are needed to study a broader range of biodiversity and ecosystem related questions as well as exploring positive futures.

Large potential for crop production adaptation depends on available future varieties - Florian Zabel; Christoph Müller; Joshua Elliott; Sara Minoli; Jonas Jägermeyr; Julia M. Schneider; James A. Franke; Elisabeth Moyer; Marie Dury; Louis Francois; Christian Folberth; Wenfeng Liu; et al. (Global Change Biology, 2021)
Climate change affects global agricultural production and threatens food security. Faster phenological development of crops due to climate warming is one of the main drivers for potential future yield reductions. To counter the effect of faster maturity, adapted varieties would require more heat units to regain the previous growing period length. In this study, we investigate the effects of variety adaptation on global caloric production under four different future climate change scenarios for maize, rice, soybean, and wheat. Thereby, we empirically identify areas that could require new varieties and areas where variety adaptation could be achieved by shifting existing varieties into new regions. The study uses an ensemble of seven global gridded crop models and five CMIP6 climate models. We found that 39% (SSP5‐8.5) of global cropland could require new crop varieties to avoid yield loss from climate change by the end of the century. At low levels of warming (SSP1‐2.6), 85% of currently cultivated land can draw from existing varieties to shift within an agro‐ecological zone for adaptation. The assumptions on available varieties for adaptation have major impacts on the effectiveness of variety adaptation, which could more than half in SSP5‐8.5. The results highlight that region‐specific breeding efforts are required to allow for a successful adaptation to climate change.

Adaptation of global land use and management intensity to changes in climate and atmospheric carbon dioxide - Peter Alexander; Sam Rabin; Peter Anthoni; Roslyn Henry; Thomas A. M. Pugh; Mark D. A. Rounsevell; Almut Arneth (Global Change Biology, 2018)
Land use contributes to environmental change, but is also influenced by such changes. Climate and atmospheric carbon dioxide ( CO 2 ) levels’ changes alter agricultural crop productivity, plant water requirements and irrigation water availability. The global food system needs to respond and adapt to these changes, for example, by altering agricultural practices, including the crop types or intensity of management, or shifting cultivated areas within and between countries. As impacts and associated adaptation responses are spatially specific, understanding the land use adaptation to environmental changes requires crop productivity representations that capture spatial variations. The impact of variation in management practices, including fertiliser and irrigation rates, also needs to be considered. To date, models of global land use have selected agricultural expansion or intensification levels using relatively aggregate spatial representations, typically at a regional level, that are not able to characterise the details of these spatially differentiated responses. Here, we show results from a novel global modelling approach using more detailed biophysically derived yield responses to inputs with greater spatial specificity than previously possible. The approach couples a dynamic global vegetative model ( LPJ ‐ GUESS ) with a new land use and food system model ( PLUM v2), with results benchmarked against historical land use change from 1970. Land use outcomes to 2100 were explored, suggesting that increased intensity of climate forcing reduces the inputs required for food production, due to the fertilisation and enhanced water use efficiency effects of elevated atmospheric CO 2 concentrations, but requiring substantial shifts in the global and local patterns of production. The results suggest that adaptation in the global agriculture and food system has substantial capacity to diminish the negative impacts and gain greater benefits from positive outcomes of climate change. Consequently, agricultural expansion and intensification may be lower than found in previous studies where spatial details and processes consideration were more constrained.

Convergence of bark investment according to fire and climate structures ecosystem vulnerability to future change - Adam F. A. Pellegrini; William R. L. Anderegg; C. E. Timothy Paine; William A. Hoffmann; Tyler Kartzinel; Sam S. Rabin; Douglas Sheil; Augusto C. Franco; Stephen W. Pacala (Ecology Letters, 2017)
Fire regimes in savannas and forests are changing over much of the world. Anticipating the impact of these changes requires understanding how plants are adapted to fire. In this study, we test whether fire imposes a broad selective force on a key fire‐tolerance trait, bark thickness, across 572 tree species distributed worldwide. We show that investment in thick bark is a pervasive adaptation in frequently burned areas across savannas and forests in both temperate and tropical regions where surface fires occur. Geographic variability in bark thickness is largely explained by annual burned area and precipitation seasonality. Combining environmental and species distribution data allowed us to assess vulnerability to future climate and fire conditions: tropical rainforests are especially vulnerable, whereas seasonal forests and savannas are more robust. The strong link between fire and bark thickness provides an avenue for assessing the vulnerability of tree communities to fire and demands inclusion in global models.